2014
DOI: 10.1007/s10152-014-0408-1
|View full text |Cite
|
Sign up to set email alerts
|

It’s not what it looks like: molecular data fails to substantiate morphological differences in two sea hares (Mollusca, Heterobranchia, Aplysiidae) from southern Brazil

Abstract: Species of sea hares have been recognized traditionally based on morphological traits, mainly the radula, external coloration, and reproductive anatomy. However, recent studies have shown substantial color variation in some sea slug species. Molecular data have been successfully used to differentiate morphologically similar species of ''opisthobranchs'' and resolve questions on the taxonomic value of color. The objective of this paper is to use molecular data in an attempt to elucidate whether specimens of Apl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A complicating factor, however, is that opisthobranch molluscan morphology may be affected by the diet itself (Trowbridge, 1997). Indeed, a recent study in Aplysia brasiliana showed that the molecular biology of related species was nearly identical, but there were significant differences in radular teeth morphology (de Oliveira Saad et al, 2014). Studies of the radula have focused primarily on the teeth covering its surface.…”
Section: Discussionmentioning
confidence: 99%
“…A complicating factor, however, is that opisthobranch molluscan morphology may be affected by the diet itself (Trowbridge, 1997). Indeed, a recent study in Aplysia brasiliana showed that the molecular biology of related species was nearly identical, but there were significant differences in radular teeth morphology (de Oliveira Saad et al, 2014). Studies of the radula have focused primarily on the teeth covering its surface.…”
Section: Discussionmentioning
confidence: 99%
“…Aplysia's radula is morphologically distinct from Spekia's as it has more teeth per row (one broader central tooth and on either side approximately 20 small, isodont, hook-like teeth; e.g. [100]) and possesses plain and rather thin odontophores. However, the aims of the past studies on the soft grasper development and of subsequent research [98,101,102] were not on determining the function of radular teeth, as they were not included in the robotic design.…”
Section: Biomimeticsmentioning
confidence: 99%
“…Unfortunately, this dispute will remain open, at least in the short term, as the most recently published accounts (e.g., Leite and Haimovici, 2006;Flores-Valle et al, 2018, Lima et al, 2020 andothers) do not describe the morphology in sufficient detail for useful comparisons. Nonetheless, distinct morphotypes in genetically homogeneous species populations (either sympatric or allopatric) have been reported in marine mollusks (Saad et al, 2014), including cephalopods (van der Vyver et al, 2016;González-Gómez et al, 2018). This suggests that the lack of supraocular cirri in our specimens may be the result of phenotypic variability.…”
Section: Callistoctopus Furvus Descriptionsmentioning
confidence: 68%